‘Colleaguography’ in place of cholangiography, to prevent bile duct injury during laparoscopic cholecystectomy - Kapoor, Vinay K. (J Minim Access Surg, 2019)
Bile duct injury (BDI) is not uncommon during laparoscopic cholecystectomy (LC). Intra-operative cholangiography (IOC) has been recommended to reduce the risk of BDI during LC. Facilities for IOC are, however, scarcely available in India. The author suggests ‘in vicinity colleaguography’ (IVC) – opinion of a surgical colleague in vicinity – as an easy alternative to IOC.